Application of Tonsil-Derived Mesenchymal Stem Cells in Tissue Regeneration: Concise Review. (25th July 2019) - Oh, Se-Young; Choi, Young Min; Kim, Ha Yeong; Park, Yoon Shin; Jung, Sung-Chul; Park, Joo-Won; Woo, So-Youn; Ryu, Kyung-Ha; Kim, Han Su; Jo, Inho
Abstract : Since the discovery of stem cells and multipotency characteristics of mesenchymal stem cells (MSCs), there has been tremendous development in regenerative medicine. MSCs derived from bone marrow have been widely used in various research applications, yet there are limitations such as invasiveness of obtaining samples, low yield and proliferation rate, and questions regarding their practicality in clinical applications. Some have suggested that MSCs from other sources, specifically those derived from palatine tonsil tissues, that is, tonsil-derived MSCs (TMSCs), could be considered as a new potential therapeutic tool in regenerative medicine due to their superior proliferation rate and differentiation capabilities with low immunogenicity and ease of obtaining. Several studies have determined that TMSCs have differentiation potential not only into the mesodermal lineage but also into the endodermal as well as ectodermal lineages, expanding their potential usage and placing them as an appealing option to consider for future studies in regenerative medicine. In this review, the differentiation capacities of TMSCs and their therapeutic competencies from past studies are addressed. Stem Cells   2019;37:1252–1260 : Abstract : Schematic illustration of lineage differentiation of tonsil-derived mesenchymal stem cells.